2018
DOI: 10.1590/1678-457x.20217
|View full text |Cite
|
Sign up to set email alerts
|

Interference of germination time on chemical composition and antioxidant capacity of white sesame (Sesamum Indicum)

Abstract: The consumption of white sesame has become a healthy option for those who are concerned about health and wish to reduce oxidative stress. The germination has been used an effective method to increase the nutrients availability and thus provide a better nutritional quality of these seeds. Due to the lack of researches about sesame germination the objective of this study was to evaluate the different times of germination on the chemical composition (moisture, fat, protein and ashes), the antioxidant capacity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…23 However, the higher protein content of the germinated (TBF) samples (∼28%), when compared with that of the control (TBA) sample (17%), may be due to the breakdown of more complex sugars and the remaining matrix of nutrients available within the structure, to expose more amino acids. 26 The observations presented in this study agreed with the past report 27 on a higher protein content for biscuits from germinated sesame seeds.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…23 However, the higher protein content of the germinated (TBF) samples (∼28%), when compared with that of the control (TBA) sample (17%), may be due to the breakdown of more complex sugars and the remaining matrix of nutrients available within the structure, to expose more amino acids. 26 The observations presented in this study agreed with the past report 27 on a higher protein content for biscuits from germinated sesame seeds.…”
Section: Methodssupporting
confidence: 92%
“…Notably, the control sample (TBA) had the highest acceptability, which might be due to the fact that consumers are familiar with it. However, the low acceptability of the appearance of sample TBF might be connected to a deep brown coloration developed (as opposed to the cream color of other samples) during the germination process of the Benniseeds . This observation is similar to the least acceptable appearance reported for biscuits produced from germinated sesame seeds .…”
Section: Resultsmentioning
confidence: 53%
“…Therefore, there is need to explore the nutritional qualities of these crops in the production of complementary food for children due to their nutrient composition and accessibility to many low-income homes. Besides, the germination of QPM has the advantage of breaking down the complex sugars and other matrix of the nutrients available within the QPM, to make more protein and amino acids available (Mares et al 2018), while fermentation caused the reduction of these organic portions through the increase in the metabolic activities of the microbes (Olagunju and Ifesan 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To further exploit the benefits of flaxseeds, in health and nutrition context, it can be subjected to processing treatment like sprouting during which varied metabolic activities occur in seedling and there is mobilization of reserve material from seedling in the growing sprouts. It was found that free amino acids, iron, zinc, and manganese contents, antioxidant capacity,total phenolic compounds,overall nutritional quality and digestibility of sprouted flaxseeds enhanced while levels of fat, protein, ash (Kajla et al., 2017), anti‐nutritional and toxic compounds like phytic acid, trypsin inhibitor and cyanogenic glycoside decreased, owing to sprouting (Mares et al., 2018). It has also been reported that germination increased the phytochemicals and different compounds, that is, total phenolics, flavonoids, and vitamin C in sprouted seeds (Pajak et al., 2014; Pajak et al, 2014; Wang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%